IMPACT OF ROAD DEVELOPMENT ON ECONOMIC GROWTH AND ACCESSIBILITY IMPROVEMENT IN LAHOMI DISTRICT, WEST NIAS - Selviana Ginting; Wahyu Hidayat; Cut Nuraini; Feby Milanie (Bulletin of Engineering Science, Technology and Industry, 2025)
This study aims to analyze the impact of road construction on accessibility, mobility, and changes in socio-economic characteristics of the community in Lahomi District, West Nias. Road construction in this area, which involves improving 67.45 km of district road infrastructure, focuses on improving access to economic centers, education, and health services. The results of the study indicate that improving road infrastructure significantly increases community accessibility to markets, public facilities, and economic resources. In addition, changes in social mobility occur with the increasing ability of people to move between villages and to economic centers, as well as supporting greater economic diversification, with a shift from the agricultural sector to the trade, services, and small industry sectors. Although positive impacts have been achieved, Lahomi District still lags behind other areas in North Sumatra in terms of infrastructure quality and accessibility. This study suggests the need for more attention to infrastructure maintenance, inclusive development management, and sustainable development planning to ensure equitable benefits and avoid negative impacts that may arise from rapid socio-economic change.